2014
DOI: 10.1002/ep.11969
|View full text |Cite
|
Sign up to set email alerts
|

Application of a compound containing silica for removing ammonium in aqueous media

Abstract: In the present investigation, removal of ammonium from aqueous solutions by a compound containing silica was considered. The compound was a waste of ferrosilicon compound produced during Ferro-alloy manufacturing. The results showed that an increase in the pH of solution up to 7 caused a rapid increase in the adsorbed ammonium to 36.21 mg/g. But adsorbed ammonium was decreased to 26.51 mg/g as the initial pH reached to 10. The amount of adsorbed ammonium was increased with contact time and initial ammonium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…31 The presence of various binding groups on the surface of adsorbent, especially ionizable -OH groups, would be beneficial for the adsorption of cationic species such as BY2. 28 It can be observed that the intensity of the peak associated with the -OH group diminished after the adsorption of BY2, which confirmed the significant role of this peak in the adsorption process. Compared to MMT, the spectra of dye-loaded clay showed two additional peaks at 1418…”
Section: Ft-ir Analysissupporting
confidence: 62%
“…31 The presence of various binding groups on the surface of adsorbent, especially ionizable -OH groups, would be beneficial for the adsorption of cationic species such as BY2. 28 It can be observed that the intensity of the peak associated with the -OH group diminished after the adsorption of BY2, which confirmed the significant role of this peak in the adsorption process. Compared to MMT, the spectra of dye-loaded clay showed two additional peaks at 1418…”
Section: Ft-ir Analysissupporting
confidence: 62%
“…Moreover, the peak placed at 480 cm -1 reflects Si-O-Si bending vibration [29,34]. The diatomite structure consists of siloxane groups or -Si-O-Si-bridges with oxygen atoms that can act as an adsorptive site for the adsorption of target pollutants [26].As shown in of hydroxyl groups and free silanol group (Si-OH) in the adsorption process.…”
Section: Ft-ir Analysismentioning
confidence: 97%
“…wherek 2ads (g/mg.min)is the pseudo-second order reaction rate constant [20,29]. The intra- where q t (mg/g), k p (mg/g.min 0.5 ) and Care the amount of adsorbed dye at time t, the rate constant and intercept of the plot, respectively [23].…”
Section: Kinetic Studymentioning
confidence: 99%
See 2 more Smart Citations